PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING PADA UPT SUNGAI DUKU PEKANBARU - Ali Umar; Suarni Norawati (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
Performance appraisal is an important thing for every leader of an organization, both public and private organizations. Many factors affect performance either directly or indirectly. This research was conducted at UPT Sungai Duku Pekanbaru and this study aims to determine the effect of motivation on performance, motivation on organizational commitment and the effect of organizational commitment on performance. This study uses primary data and secondary data, where primary data were obtained from seventy-three employees as samples. Data was collected by means of interviews, questionnaires and documentation. Data analysis was carried out using the SEM (Structural Equition Model) method and assisted by the SmartPLS version 3.00 program. The results of this study conclude that there is a significant influence of the motivational variable on performance, a significant influence of motivation on organizational commitment and there is a significant influence of organizational commitment on performance.